An Enhanced Modulator Concept for Modular Multilevel Converter - Schröder, Markus; Henninger, Stefan; Jäger, Johann (16th Conference on Power Electronics and Applications, 2014)
This paper deals with an enhanced modulator concept for the Modular Multilevel Converter. Based on an overview on existing concepts including module sorting algorithms and measurement results from a hardware-setup in laboratory, a new concept is developed. Measurement results of the implemented new algorithm for module selection and capacitor energy balancing in various operating points of the converter are presented and analyzed in detail. This elaboration is completed with a classification of the suggested modulator concept compared to established concepts.
Keywords: Modulation strategy; Multilevel converter; Pulse Width Modulation